2011
DOI: 10.1007/s12032-011-9928-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HCV infection in renal cell carcinoma patients

Abstract: Chronic infections with hepatitis C virus (HCV) are frequently pronounced in the etiology of malignancies especially in hepatocellular carcinoma. The association between HCV and risk of renal cell carcinoma (RCC) development has been stated recently. The authors retrospectively evaluated hepatitis serology for HCV and HBV in patients who had RCC diagnosis between 2005 and 2010 in six oncology centers. Control group was also included from the three different published studies that hepatitis serology studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Also, there were too much missing data (66%) in this study which may have contributed to bias to their analyses [22]. Budakoğlu et al did not confirm the anti-HCV antibody-positive status of the subjects with HCV RNA which could have resulted in a bias in their analysis since anti-HCV antibodies can be falsely positive due to old infection or secondary to cross reactivation with other infections [40]. Hofmann et al excluded 623 HCV-infected subjects from the analyses due to incomplete information [42].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, there were too much missing data (66%) in this study which may have contributed to bias to their analyses [22]. Budakoğlu et al did not confirm the anti-HCV antibody-positive status of the subjects with HCV RNA which could have resulted in a bias in their analysis since anti-HCV antibodies can be falsely positive due to old infection or secondary to cross reactivation with other infections [40]. Hofmann et al excluded 623 HCV-infected subjects from the analyses due to incomplete information [42].…”
Section: Discussionmentioning
confidence: 93%
“…Increased prevalence of anti-HCV was found in patients with RC cases as compared to control group [41]. However, Budakoğlu et al found no significant increase in HCV positivity in RC patients compared to healthy control group [40] (Table 5). …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table in the Supplement, eleven studies were considered at low risk of bias (NOS score ≥ 7), 18‐21,23,24,27,28,30‐32 the other 5 were deemed to have a high risk of bias (NOS score < 7) 22,25,26,29,33 …”
Section: Resultsmentioning
confidence: 99%
“…Five of them confirmed KC by pathologic reports and the other 11 by ICD code of diagnostic registries. Thirteen studies considered confounding factors, either through matching patients or adjustment analysis, 2 did not perform relevant analysis, 18,29 and the other 1 had no description on it. 26…”
Section: Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation